Heaving and pitching oscillating foil propulsion in ground effect. (May 2016) - Mivehchi, Amin; Dahl, Jason; Licht, Stephen
Abstract: A detailed series of experiments is performed to investigate the 'ground effect' experienced by propulsive flapping foils operating near a solid boundary. A high aspect ratio foil is towed at constant speed and oscillated in pitch and heave at varying distances from a rigid wall. It is shown that this distance has a significant impact on the lift and thrust forces generated by the foil, both in the time averaged mean forces and the phase averaged periodic forces. For some thrust producing kinematics, the instantaneous force profile may change significantly without altering the time averaged mean force; thus, mean force measurements alone are not sufficient to indicate the proximity, or the effect, of the solid boundary. Results are presented across a wide range of thrust generating kinematics, showing that the strength of the ground effect can be modulated, for any achievable level of thrust, through appropriate selection of kinematics. This finding in particular has significance for underwater vehicles propelled by oscillating foil thrusters, as it follows that the sensitivity of the thrusters to ground effect can be controlled independently of the desired thrust. While propulsive efficiency is increased slightly near the wall for some kinematics, in general this does not occur for kinematics where a strong ground cushion (repulsion) effect is observed. Finally, the results suggest that span-wise flow around the tip of the foil is important in determining whether the foil is repelled from or pulled into the wall.